Chalcogen-bonded donor–acceptor complexes of 5, 6-dicyano[1, 2, 5]selenadiazolo[3, 4-b]pyrazine with halide ions. (13th July 2022) - Radiush, Ekaterina A.; Pritchina, Elena A.; Chulanova, Elena A.; Dmitriev, Alexey A.; Bagryanskaya, Irina Yu; Slawin, Alexandra M. Z.; Woollins, J. Derek; Gritsan, Nina P.; Zibarev, Andrey V.; Semenov, Nikolay A.
Abstract : With halides X − (X = Cl, Br, I) 5, 6-dicyano-[1, 2, 5]selenadiazolo[3, 4- b ]pyrazine 1 forms chalcogen-bonded complexes [1 –X] − structurally defined by XRD. UV/Vis spectra of [1 –X] − feature red-shifted charge-transfer bands in the Vis part. Abstract : New complexes of 5, 6-dicyano[1, 2, 5]selenadiazolo[3, 4- b ]pyrazine 1 with halide anions X − (X = Cl, Br, I) are prepared. With XRD, DFT, QTAIM and NBO, it is found that the complexes are formed via Se–X − chalcogen bonding. Diffuse reflectance spectroscopy of polycrystalline samples and UV/Vis spectroscopy of solutions of [1 –X] − reveal significant spectral changes upon complexation. According to time-dependent DFT, these changes are caused by the appearance of charge transfer bands (p-AO(X) → LUMO(1 )) in the visible region. The equilibrium constants for complex formation were measured with UV/Vis spectrophotometric titration and found to be significantly lower than those reported for structurally similar complexes of 3, 4-dicyano-1, 2, 5-selena(tellura)diazoles, which indicates relatively weak chalcogen bonding in [1 –X] − . Dispersion-corrected DFT reproduces well the Gibbs free energies of complexation. The QTAIM descriptors and NBO analyses using second-order perturbation theory suggest that the Se–X − chalcogen bonding in the studied complexes is predominantly electrostatic and dispersive in nature with a small but significant contribution from donor–acceptor (or orbital) interactions. The strongest contribution to the latter comes from negative hyperconjugation, i.e. donation of the electron density of the lone-pair of X − onto the σ *–MO of the Se–N bond of 1 .